Changes between Version 2 and Version 3 of u/johannjc/scratchpad4
- Timestamp:
- 09/30/15 16:42:07 (9 years ago)
Legend:
- Unmodified
- Added
- Removed
- Modified
-
u/johannjc/scratchpad4
v2 v3 55 55 Now if we write the equation as 56 56 57 $\partial_t T = B_ i\partial_j T^{\lambda+1} + C_j \partial_j T^\lambda T' + D_{ij} \partial_i\partial_j T^{\lambda+1} + E_{ij} \partial_i \partial_j T^\lambda T'$57 $\partial_t T = B_j \partial_j T^{\lambda+1} + C_j \partial_j T^\lambda T' + D_{ij} \partial_i\partial_j T^{\lambda+1} + E_{ij} \partial_i \partial_j T^\lambda T'$ 58 58 59 59 we get expressions for 60 61 $A = \frac{1}{\Delta t}$ 60 62 61 63 $B_j = \frac{\kappa_\parallel \left ( \phi-\psi\lambda \right )}{\lambda+1} \partial_i n b_i b_j $ … … 69 71 We then need expressions for 70 72 71 $ \partial_t T = \frac{T'_0 - T_0}{\Delta t}$ 73 $ \partial_t T = A \left ( T'_0 - T_0 \right )$ 74 72 75 $ \partial_j T^{\lambda+1} = \frac{T^{\lambda+1}_{\hat{j}} - T^{\lambda+1}_{-\hat{j}}}{2 \Delta x}$ 73 76 … … 80 83 We can also write the equation as 81 84 82 $\ alpha_0 T'_0 + \displaystyle \sum_{\pm i} \alpha_{\pm i} T'_{\pm \hat{i}} + \sum_{\pm i, \pm j,|i| \ne |j|} \alpha_{\pm i, \pm j} T'_{\pm \hat{i} \pm \hat{j}} = \beta$85 $\beta = \alpha_0 T'_0 + \displaystyle \sum_{\pm i} \alpha_{\pm i} T'_{\pm \hat{i}} + \sum_{\pm i, \pm j,|i| \ne |j|} \alpha_{\pm i, \pm j} T'_{\pm \hat{i} \pm \hat{j}}$ 83 86 84 87 and then work out the coefficients for the matrix equation 85 88 89 $\alpha_0 = -A -2E_{ii}T_0^\lambda = n \kappa_\parallel \psi$ 90 91 $\alpha_{\pm i} = \pm C_iT^\lambda_{\pm hat{i}} + E_{ii}T_{\pm \hat{i}}^\lambda$ 92